Screening of variable importance for optimizing electrodialytic remediation of heavy metals from polluted harbour sediments - Pedersen, Kristine Bondo; Lejon, Tore; Ottosen, Lisbeth M.; Jensen, Pernille E. (Environmental Technology, 2015)
Published version, also available at http://dx.doi.org/10.1080/09593330.2015.1028470 Using multivariate design and modelling, optimal conditions for electrodialytic remediation (EDR) of heavy metals were determined for polluted harbour sediments from Hammerfest harbour located in the geographic Arctic region of Norway. The comparative importance of the variables; current density, remediation time, light/no light, the liquid-solid ratio and stirring rate of the sediment suspension were determined in 15 laboratory scale EDR experiments by projection to latent structures (PLS). The relation between the X matrix (experimental variables) and the Y matrix (removal efficiencies) was computed and variable importance in the projection was used to assess the influence of the experimental variables. Current density and remediation time proved to have the highest influence on the remediation of the heavy metals Cr, Cu, Ni, Pb and Zn in the studied experimental domain. In addition it was shown that excluding the acidification time improved the PLS model, indicating the importance of applying a limited experimental domain that covers the removal phases of each heavy metal in the specific sediment. Based on PLS modelling the optimal conditions for remediating the Hammerfest sediment was determined; operating in the experimental domain of 0.5-0.8 mA/cm2 and a remediation time after acidification of 450-570 hours met acceptable levels according to Norwegian sediment quality guidelines